Digitalization of Teacher Performance Evaluation through a Web-Based APIPA Model to Realize Impactful Learning in Junior High Schools (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
This study aims to examine the effectiveness of the web-based APIPA (Assessment, Planning, Implementation, Product, Appreciation) evaluation model in improving mathematics teachers' performance and exploring its relationship with the effectiveness of impactful learning at the junior high school level. The method used is mixed methods with an explanatory sequential design. Quantitative data were collected through pretest-posttest and analyzed using descriptive statistics, Shapiro-Wilk normality test, paired samples t-test, and N-Gain. Further analysis used Rasch Model and structural equation modeling (SmartPLS 4) to assess the validity of the instruments and the relationship between the model dimensions. Meanwhile, qualitative data were obtained through in-depth interviews and analyzed using NVivo to uncover teachers' instructional reflections on the implementation of the model. The results showed that the web-based APIPA model effectively improved teachers' performance significantly on all indicators (t = -88.7; p < 0.001). The average N-Gain value of 0.3860 indicates moderate and uniform improvement. Rasch analysis shows that the instrument has high structural validity, homogeneous score distribution, and is free from participant bias. Path analysis reveals interactions between model dimensions that reinforce each other in supporting impactful learning. Additionally, differences in instructional reflection between high- and low-scoring teachers suggest that this model also functions as a catalyst for the formation of evaluative awareness. The conclusions of this study affirm that the APIPA model is not merely an evaluation tool but also a reflective-transformational framework capable of driving improvements in the quality of digital, systemic, and sustainable learning.